PENGEMBANGAN MOBILE LEARNING (M-LEARNING) BERBASIS MOODLE SEBAGAI ALTERNATIF MEDIA PEMBELAJARAN DI TINGKAT SMK - Ulfah, Ni'mah Naafi'atul; Beni Habibi; Tri Mulyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the development of M-Learning based on Moodle as an alternative learning media to improve independence and critical thinking skills in the Computer and Network Engineering Concentration subject at SMK Negeri 1 Dukuhturi. M-Learning (Mobile Learning) refers to the use of digital technology, especially the internet, to support the learning process. In the world of education, M-Learning has become one of the most effective approaches in facilitating flexible, efficient, and interactive access to education. Teachers and students will gain flexibility in learning. M-Learning allows learning to be done anytime and anywhere as long as there is an internet connection, so it is expected to trigger critical thinking skills and student independence. The approach used in this study is Research and Development or R&D, which functions to validate and develop products. The findings of this study indicate that the development of Moodle-based M-Learning as an alternative learning media can improve students' independence and critical thinking skills. The attractive features of M-learning make students more active during the learning process, and the existence of discussion forums and collaborations allows students to discuss, share ideas or work together on projects online. Although the results obtained are quite positive, this study also noted several challenges, such as limited internet access, lack of direct interaction between students and teachers and friends, as well as potential distractions and lack of motivation from the environment. Therefore, this research recommends the need for increased training and access to technology, teacher skills development, increased motivation and self-discipline of students, and the provision of quality materials.